Fiber optic vibration sensor using bifurcated plastic optical fiber - Abdullah, M. (American Institute of Physics Inc., 2016)
An extrinsic fiber optic vibration sensor is demonstrated for a fiber optic displacement sensor based on a bundled multimode fiber to measure a vibration frequency ranging from 100 until 3000 Hz. The front slope has a sensitivity of 0.1938mV/mm and linearity of 99.7 within a measurement range between 0.15-3.00 mm. By placing the diaphragm of the concave load-speaker within the linear range from the probe, the frequency of the vibration can be measured with error percentage of less than 1.54. The graph of input against output frequency for low, medium and high frequency range show very high linearity up to 99. Slope for low, medium, and high frequency range are calculated as 1.0026, 0.9934, and 1.0007 respectively. Simplicity, long term stability, low power consumption, wide dynamic and frequency ranges, noise reduction, ruggedness, linearity and light weight make it promising alternative to other well-establish methods for vibration frequency measurement. Â© 2016 Author(s).